1990
DOI: 10.1002/art.1780330508
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic associations of scleroderma‐related antinuclear antibodies

Abstract: Patients selected for the presence of sclerodermarelated antibodies (anti-DNA-topoisomerase I [antitop0 I; n = 431, anticentromere antibody [ACA; n = 631, or anti-Pm-Scl [n = 121) were studied for class I and class I1 major histocompatibility complex antigens, as well as for Gm and Km allotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
3
6

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 47 publications
6
63
3
6
Order By: Relevance
“…Consistent with previous studies (1 1,13), the IB reaction of all anti-PM-Scl sera against whole HeLa cell extract was weak. In our previous study, 59% of 39 sera reacted with the 100-kd and 41% with the 70-kd protein (13).…”
Section: Results Of Immunoblotting With the Immunoprecipitatessupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies (1 1,13), the IB reaction of all anti-PM-Scl sera against whole HeLa cell extract was weak. In our previous study, 59% of 39 sera reacted with the 100-kd and 41% with the 70-kd protein (13).…”
Section: Results Of Immunoblotting With the Immunoprecipitatessupporting
confidence: 92%
“…This demonstrates a high degree of consistency in the response of different patients with anti-PM-Scl antibodies. The similarity of response of most patients is interesting in view of the very strong association of the production of anti-PMScl with the HLA-DR3 antigen (1,5,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a previous study has suggested that the frequency of HLA-DR7 was increased (12). Anti-PM-Scl was associated with the HLA-DR3, DQ2 haplotype in all instances, as reported in several other studies (29,40,41).…”
Section: Discussionsupporting
confidence: 88%